ANALYSIS OF SELF EFFICACY, MENTAL LOAD AND STUDENTS LEARNING MOTIVATION SD NEGERI 1 BERKAT - Giran Suares; Hetilaniar; Aldo Pratama (SMART: Journal of Multidisciplinary Educational, 2023)
The formulation of the problem in this research is what is the self-efficacy, mental load, andlearning motivation of students at SD Negeri 1 Berkat? The purpose of this research is todetermine the self-efficacy, mental load, and learning motivation of students at SD Negeri 1Berkat. This research method uses qualitative methods. The main subjects of this research areclass V students at SD Negeri 1 Berkat, while the accompanying or supporting subjects in thisresearch are class V teachers at SD Negeri 1 Berkat. Data collection techniques are observation,interviews, and documentation, data analysis techniques are data reduction, data presentation,and drawing conclusions. Based on the research results, it was found that the self-efficacy ofclass V students at SD Negeri 1 Berkat as a whole was classified as having sufficient selfconfidence. The students of SD Negeri 1 Berkat were able to complete their assignments on time,although overall there were still some students who were not able to do so (a small portion). SDNegeri 1 Berkat students have confidence in being able to complete their assignments at school.Apart from that, from the results of interviews regarding students' responses regarding selfconfidence, students at SD Negeri 1 Berkat stated that they lacked self-confidence, but there were also those who stated what aspects of the beliefs they meant and were doubtful about these beliefs. From the results of the interview, it was found that SD Negeri 1 Berkat was confident that they could complete the assignments according to the desired target, and tried as hard as possible to complete the assignments that had been given based on the students' self-confidence. The results of the research show that the mental condition of class V students when participating in the teaching and learning process at school is in the good category.